1996
DOI: 10.3354/meps131097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a marine reserve on the distribution of coral reef fishes in Barbados

Abstract: High population densities of larger fish withln reserves could result in emigrat~on of fish to surrounding non-reserve areas, producing a gradient of abundance and mean size across the reserve boundaries. The difference in fish abundance and size between reserve and non-reserve should be higher for sedentary than for mobile species and for highly catchable than for less catchable species. To test these hypotheses we estimated the abundance and size of fishes by trapping and visual census on fringlng reefs in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(205 citation statements)
references
References 16 publications
7
194
2
2
Order By: Relevance
“…For Mombasa Reserve (McClanahan & Mangi 2000), we used catch rather than mean fish size data, because mean size masks abundance and/or biomass patterns while catch is a direct measure of fisheries benefit. For Barbados Reserve (Rakitin & Kramer 1996), we used catch rather than density data as density gradients do not always reflect true spillover patterns (as discussed below), but we report both measures in Appendix 1 (see supplementary material at URL http://www.ncl.ac.uk/ icef/EC_Supplement.htm) to help illustrate this point. Finally, for Columbretes Reserve (Goni et al 2006), we used catch per unit effort (CPUE) rather than catch per unit area (CPUA) data because the former were measured both inside and outside the reserve while the latter were only measured outside the reserve, and thus model fits were more accurate (and conservative) with CPUE data.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For Mombasa Reserve (McClanahan & Mangi 2000), we used catch rather than mean fish size data, because mean size masks abundance and/or biomass patterns while catch is a direct measure of fisheries benefit. For Barbados Reserve (Rakitin & Kramer 1996), we used catch rather than density data as density gradients do not always reflect true spillover patterns (as discussed below), but we report both measures in Appendix 1 (see supplementary material at URL http://www.ncl.ac.uk/ icef/EC_Supplement.htm) to help illustrate this point. Finally, for Columbretes Reserve (Goni et al 2006), we used catch per unit effort (CPUE) rather than catch per unit area (CPUA) data because the former were measured both inside and outside the reserve while the latter were only measured outside the reserve, and thus model fits were more accurate (and conservative) with CPUE data.…”
Section: Synthesismentioning
confidence: 99%
“…The expectation that spillover from marine reserves will produce abundance gradients with distance from the reserve, with a shape that depends on species mobility and catch rates, was first described over a decade ago (Rakitin & Kramer 1996) and later refined and modelled (Kaunda-Arara & Rose 2004; Goni et al 2006). We expanded on these previous modelfitting approaches and estimated spillover by fitting three model forms (exponential decay, Eq.…”
Section: Statistical Models Of Potential Spillovermentioning
confidence: 99%
“…However, only a few studies have experimentally tested for spillover through increased captures in adjacent fished areas, often along density gradients: Barbados (Rakitin & Kramer 1996), Kenya (McClanahan & Mangi 2000, Kaunda-Arara & Rose 2004 and Apo Island in the Philippines (Abesamis & Russ 2005). In the Mediterranean, few data are available to assess the value of MPAs as a source of biomass to surrounding fisheries (Goñi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MPAs are predicted to benefit adjacent fisheries through 2 mechanisms: (1) net emigration of adults and juveniles across borders, termed 'spillover'; and (2) increased production and export of pelagic eggs and larvae (Gell & Roberts 2003, Kaunda-Arara & Rose 2004, Abesamis & Russ 2005, Sale et al 2005. Spillover of juvenile and adult fish to surrounding non-protected areas could result from random movements of individuals from MPAs to outside their borders or by directed movements over a large home range (Rakitin & Kramer 1996, Kramer & Chapman 1999, Tremain et al 2004. Emigration may also occur through ontogenetic habitat shifts (Cocheret de la Moriniere et al 2002, Nagelkerken & van der Velde 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Rakitin and Kramer (1996) suggested that a decreasing gradient in the abundance or biomass of targeted fish from high at inside to low at outside the reserve may indicate spillover. The inside sites have also the presence of sexually matured individuals as compared with the outside sites ( Figure 5) most likely because of the protection offered by the MPAs.…”
Section: Aundanao Mpamentioning
confidence: 99%